Effectiveness of Ginger Extract (Zingiber officinale) and Turmeric (Curcuma domestica) against the mortality of the Armyworm (Spodoptera litura) - Santi, Idum Satia; Manto, Agus; Noviana, Githa (Akademi Komunitas Perkebunan Yogyakarta, 2024)
Some types of plants can serve as plant-based insecticides. Ginger (Zingiber officinale) and Turmeric (Curcuma domestica) are ingredients that are often used as pesticides on various plant pests. Spodoptera litura itself is a pest that is quite annoying in various plants. The study aimed to examine ginger (Zingiber officinale) and turmeric (Curcuma domestica) extracts as insecticides to control armyworms (Spodoptera litura). The research was carried out in Pelemsari Village, Prenggan, Kotagede, Yogyakarta from May to June 2022. The study used a Complete Random Design (RAL) with 2 factors. The first factor is the type of extract, namely ginger and turmeric. The second factor is the concentration of the extract which consists of 3 levels, namely 20%, 40%, 60% and control, each treatment is repeated 3 times. To find out the real difference between the data treatments, the observation results were analyzed with Duncan's Multiple Range Test (DMRT) at the real level of 5%. Ginger and turmeric extracts at a concentration of 20% have been able to control S. litura larvae. Ginger extract is more effective compared to turmeric extract based on the mortality test, efficacy, death rate, and feed spoilage rate of S. litura larvae. The research is still in the experimental stage in the laboratory and needs to be tested in the field to get an effective dose for armyworms.